Testing for short and long-run causality: The case of the yield spread and economic growth - Jörg Breitung; Bertrand Candelon (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
To assess the predictive content of the interest rate term spread for future economic growth, we distinguish short-run from long-run predictability by using two different approaches. First, following Dufour and Renault (1998) a test procedure is proposed to test for causality at different forecast horizons. Second, the framework of Geweke (1982) and Hosaya (1991) is used to construct a simple test for causality in the frequency domain. This methodology is applied to investigate the predictive content of the yield spread for future output growth. For U.S. data we observe good leading indicator properties at frequencies around one year and typical business cycle frequencies. Using German data we found a (rather weak) predictability at low frequencies only.
urn:nbn:de:kobv:11-10051133
Keywords: 330; Causality; Time series; Frequency domain; Prediction